Adapting to drought and extreme climate: Hunger Safety Net Programme, Kenya. (December 2020) - Maione, Carol
Highlights: HSNP targets up to 31% of pastoral communities suffering from droughts in Kenya. Cash transfers increased access to food and economic resources between 2009-2017. Policy shifts to reduce climate risks are needed to alleviate hunger and poverty. Abstract: Drought and extreme weather conditions adversely affect the capacity of rural communities to support their livelihoods. They are also major causes of food scarcity in Northern Kenya. Inability to adapt to variable and changing local climate conditions and low levels of resilience have driven hunger and malnutrition-related diseases, affecting children and elderly in particular because of their high vulnerability in the population. In response to these conditions, the Government of Kenya in 2009 established the Hunger Safety Net Programme (HSNP), now in Phase III of its implementation. The HSNP is one of the central components of the national development program, Kenya Vision 2030. Its main objectives are to achieve food security for all and promote financial inclusion through cash transfers, funded substantially by international agencies. Enlarged access to cash transfers benefits vulnerable households that have lost access to natural and agricultural resources owing both to extreme weather conditions and as a result of changing socio-economic forces. In these circumstances, those who are natural resource dependent are not able to ensure their own current and future welfare. Since implementation began in 2009, HSNP has covered 31% of the population in the poorest regions, providing support to 69, 000 households. Its expansion through additional financial resources will enable a larger number of highly vulnerable households to improve their resilience, address climate risks more effectively, and safeguard their future wellbeing. To this end, future domestic and international investments resources should target insurance programs, technical assistance, disaster risk reduction laws, natural capital protection, and compensation programs.